FROM PATRIARCHY TO PROGRESS: EXPLORING THE SHIFT IN ATTITUDES TOWARDS WOMEN’S EDUCATION LED BY TUAN GURU IN LOMBOK-INDONESIA - Ridwan , Auliya (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research, rooted in a 2022 fieldwork at Pesantren Nurul Haramain Lombok, explores the leadership of Tuan Guru Hasanain Juaini. Overseeing both male and female segments of the Pesantren, Tuan Guru Hasanain distinctively prioritizes the female Pesantren, providing diverse skill opportunities. Female students (santriwati) engage in activities traditionally associated with males, including driving, waste management, archery, music production, and android application development, etc. The study delves into Tuan Guru Hasanain’s approach, tracing it to his father’s influence, emphasizing the central role of his mother in education. These early experiences shape Tuan Guru Hasanain’s awareness of the significance of women’s education, viewing it as an investment in shaping the future. Employing qualitative observation, the research analyzes the intricate interplay of cultural, familial, and educational dynamics shaping Hasanain’s stance. This work contributes to the discourse on gender inclusivity in Islamic education, illustrating a tangible example of a Pesantren leader championing equality and empowerment through strategic educational emphasis.